Por que Barbosa? : o papel das tecnologias do imaginário sobre o vilão da Copa de 1950 no Jornal dos Sports - Rizzatti, Lucas Osório (2017)
This research seeks understanding the role played by the imaginary technologies over the figure of the 1950 World Cup major villain. The starting point is the goalkeeper Barbosa who centralizes the imaginary of the villain. The analysis developed presents how such technologies acted in order to establish this scenario, focusing on the published editions of "Jornal dos Sports" since the decisive match involving Brazil and Uruguay. The study is based on the intepretative sociology and the imaginary technologies, including aspects towards the sports journalism, mainly the brazilian one.